THE ECONOMIC ROLE OF COMMUNITY WITH MEDIUM SMALL MICRO BUSINESSES IN INCREASING PEOPLE'S WELFARE - Rochmatillah, Rochmatillah (Universitas Mataram, 2019)
Prosperous and prosperous people in a country can be seen from how the function of the country is, because creating prosperity and prosperity for the people is a function and purpose of the establishment of a country. We already know that in Indonesia there are still many gaps between